Different responses of soil CO2 and N2O emissions to simulated N deposition in forests with divergent N transformation characteristics. (2nd July 2020) - Song, Lei; Zhang, Jinbo; Jin, Guangze
Abstract: CO2 and N2 O are important greenhouse gases that are related to soil mineralization–immobilization turnover and nitrification. To explore the responses of CO2 and N2 O emissions to N deposition in forests with different N transformation characteristics, CO2 and N2 O fluxes were measured in two NH4 NO3 fertilized plots. One plot was in a temperate pine plantation in Heilongjiang Liangshui National Nature Reserve (LS) with slow and minimally coupled mineralization–immobilization turnover and a high nitrification rate. The other plot was in a subtropical bamboo forest in the Fujian Daiyun Mountain National Nature Reserve (DY) in China with rapid and coupled mineralization–immobilization turnover but a low nitrification rate. The results showed that CO2 emissions in the DY with a high mineralization rate were greater than those in the LS. Cumulative CO2 emissions were significantly enhanced by N addition in DY, but in LS, they were not affected. The mean N2 O fluxes in the control were 0.010 and 0.008 mg N m −2  hr −1 for LS and DY, respectively. High N addition stimulated N2 O emissions in both LS and DY, but the response ratio for N2 O flux in LS (8.6) was larger than that in DY (2.9). These results suggested that soils with rapid and coupled mineralization–immobilization turnover are beneficial to CO2 emissions and their positive response to N deposition. A high nitrification rate contributed to high N2 O emissions and the sensitive response of N2 O emissions to N deposition.